Pengembangan Sistem Informasi Pendataan untuk Salon Mobil dan Body Repair di PT. Isuindomas Putra (Capella Body Centre) di Kota Banda Aceh - Hermansyah; Ismail; Idwan, Harry (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
Information system development is a crucial step in increasing the effectiveness and efficiency of company operations. This research aims to understand, design, and implement a data collection information system for car salons and body repairs at PT. Isuindomas Putra (Capella Body Center) in Banda Aceh City. Qualitative descriptive research methods are used to describe phenomena that occur in real situations, by collecting data through direct observation, interviews, and literature study. The results of the analysis show that the current information system experiences several weaknesses, such as slow processing, errors in making reports, and lack of data security. Therefore, the design of the new system was carried out using software development methods based on the software development life cycle (SDLC). Development steps include requirements analysis, design, implementation, testing, and maintenance. The discussion presents the results of ongoing system analysis and new system design to improve work effectiveness at PT. Isuindomas Putra (Capella Body Center) Banda Aceh City. The conclusion states that the implementation of a car salon and body repair information system provides significant benefits for the company, while suggestions are given for further development towards integration with the inventory system and providing complete accounting reports. Thus, the development of this information system is expected to increase the company's overall operational efficiency and effectiveness.